CREDIT SUPPORT OF AGRICULTURAL ENTERPRISES IN WAR CONDITIONS - Ahres , О.; Markiv , Г.; Tomashevskyi , Ю. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
In the modern world, financial technologies play a significant role in the economy. Fintech companies introduce innovative goods and services that guarantee convenient and quick financial transactions to the market. It provides consumers with more opportunities to manage their finances and cut down the cost of financial transactions. Ukraine is also experiencing a stage of rapid development in the fintech industry. However, the potential of unrealized opportunities for the fintech companies’ development at the Ukrainian financial market is just at the stage of growing. Revitalizing the development of the financial technology market in Ukraine is a task for both the government and businesses, which contributes to the efficient implementation of new technologies in the financial sector. The research confirms that the application of fintech technologies provides new opportunities for the business entities of the Ukrainian economy due to the effective development of the financial sector. The analysis of cases of foreign fintech companies helps to identify promising development directions of the financial sector of Ukraine and to shape recommendations for Ukrainian companies engaged in this field. It is established that the development and implementation of new technologies aid Ukrainian fintech companies to increase their level of competition and provide customers with more effective innovative financial services. The expansion of international cooperation and the entry of Ukrainian fintech companies to foreign markets also contributes to the development and promotion of the Ukrainian fintech industry. The authors study the advantages and disadvantages of fintech companies' operation in the near future, since the military actions in the country slow down the pace of innovative development of financial technologies in Ukraine. It is demonstrated that examining the experience of international fintech companies may be quite instructive for estimating their level of success in integrating the cutting-edge technology and methods to acquire conventional financial services in the Ukrainian financial market. In the scientific study, the authors analyze the global experience of using fintech and the possibilities of implementing its individual elements for the Ukrainian financial market. Certain recommendations for financial market entities regarding the implementation of financial technologies of leading global companies and the possibility of using this experience in Ukraine have been suggested. The scientific article summarizes the obtained research results and the possibility of their future application in our country.